Managing Climate Variability Program - Land and Water Australia (Canberra, A.C.T. : Land & WaterAustralia, 2004)
Site contains information on the program, copies of reports, newsletter, links to related sites.
Title from title screen (viewed on 21 July 2008)
Text and graphics.
Mode of access: Internet via World Wide Web. Formerly available at: http://www.managingclimate.gov.au
Selected for archiving
Keywords: Managing Climate Variability Program; Agricultural systems -- Australia; Climatic changes -- Australia; Crops and climate -- Australia